From Oasis Archipelago to Pioneering Eldorado in Algeria's Sahara. (28th November 2018) - Amichi, F.; Bouarfa, S.; Kuper, M.; Caron, P.
Abstract: Since the 1980s, the Biskra region in Algeria's Sahara has undergone rapid agricultural change leading to territorial transformation. Horticultural production under greenhouses, associated with a rapid expansion of date palm plantations, has led to a tangible agricultural boom that is constantly pushing the boundaries of agricultural production and constitutes a true pioneering fringe. To understand the pioneering logics at work, we propose to study the pioneer fringe through three fronts, namely land, water and infrastructure. First, we analyse each front separately in order to understand its logic. In a second step, through three illustrations, we show how these fronts interpenetrate, accelerate one another or, on the contrary, constrain the pioneer fringe. The analysis of the advance of the pioneering fringe has shown that it results from the interweaving of the three main fronts and each of these combines both the actions of the state and private initiative. © 2018 John Wiley & Sons, Ltd. Résumé: Depuis les années 1980, la région de Biskra dans le Sahara Algérien a connu de fortes mutations agricoles entrainant des dynamiques de transformation territoriale. En effet, sous l'effet du développement de la production maraîchère, associée à l'expansion rapide des plantations de palmiers dattiers, on assiste à un véritable boom agricole qui ne cesse de repousser les frontières de la production agricole et constitue une véritable frange pionnière. Dans le but de comprendre les logiques pionnières à l'œuvre, nous proposons d'étudier la frange pionnière à travers trois fronts à savoir; le foncier, l'eau et les infrastructures. Dans un premier temps, nous analysons chaque entrée séparément afin d'en comprendre les logiques. Dans un second temps, à travers trois illustrations, nous montrons comment ces fronts s'interpénètrent, s'accélèrent les uns les autres ou au contraire se contraignent. L'analyse de l'avancée de la frange pionnière nous a montré qu'elle résulte de l'imbrication des trois principaux fronts et chacun de ces fronts conjugue à la fois l'action de l'État et l'initiative privée. © 2018 John Wiley & Sons, Ltd.